(untitled) (International Journal of Architecture and Urbanism, 2024)
Pedestrian paths or commonly referred to as pedestrian paths are public facilities that must exist in every place and one of them must be found in the campus area. If the pedestrian path on campus does not make it comfortable and safe, it will have an impact on the psychology of students in walking activities and prefer to use motorized vehicles. In improving the evaluation of the quality of campus environmental infrastructure that is comfortable and safe for its users, the comfort of pedestrian paths is very important for pedestrians. In this case, the comfort evaluation for pedestrian paths was held. The methods used in collecting data for this research are Descriptive Quantitative and Qualitative Methods, namely by observing directly to the research site and interviewing in private for convenience and further expressing views on pedestrian paths in the ITERA campus environment. Based on an assessment of 7 aspects, pedestrian paths or pedestrians at ITERA are lacking in terms of condition and comfort. The arrangement of the trees is also good and pedestrians also feel safe when walking. Cleanliness on the pedestrian path is clean with free space for movement. The zone that is less comfortable when traveling is in zone C because many students attend classes in the area. The expected facilities are vegetation, seating for resting and also road crossing markers.